Incentives for Pollution Control : Regulation and Public Disclosure - Foulon, Jérôme (World Bank, Washington, DC, 2015)
An increasing number of regulators have adopted public disclosure programs to create incentives for pollution control. Previous empirical analyses of monitoring and enforcement issues have focused strictly on the impact of such traditional practices as monitoring (inspections) and enforcement (fines and penalties) on polluters' environmental performance. Other analyses have separately focused on the impact of public disclosure programs. But can these programs create incentives in addition to the normal incentives of fines and penalties? The authors study the impact of both traditional enforcement and information strategies in the context of a single program, to gain insights into the relative impact of traditional (fines and penalties) and emerging (public disclosure) enforcement strategies. Their results suggest that the public disclosure strategy adopted by the province of British Columbia, Canada, has a greater impact on both emission levels and compliance status than do orders, fines, and penalties traditionally imposed by the courts and the Ministry of the Environment. But their results also demonstrate that adopting stricter standards and higher penalties also significantly affected emission levels. Policymakers, take note: 1) The presence of strong, clear standards together with a significant, credible penalty system sends appropriate signals to the regulated community, which responds by lowering pollution emissions. 2) The public disclosure of environmental performance creates strong additional incentives to control pollution.